Investigation of the mechanism of action of mefloquine and derivatives against the parasite Echinococcus multilocularis - Roman Memedovski; Matías Preza; Joachim Müller; Tobias Kämpfer; Reto Rufener; Marcus Vinicius Nora de Souza; Emerson Teixeira da Silva; Gabriel Fernandes de Andrade; Sophie Braga; Anne-Christine Uldry; Natasha Buchs; Manfred Heller; et al. (International Journal for Parasitology: Drugs and Drug Resistance, 2023)
Alveolar echinococcosis (AE) is caused by infection with the fox tapeworm E. multilocularis. The disease affects humans, dogs, captive monkeys, and other mammals, and it is caused by the metacestode stage of the parasite growing invasively in the liver. The current drug treatment is based on non-parasiticidal benzimidazoles. Thus, they are only limitedly curative and can cause severe side effects. Therefore, novel and improved treatment options for AE are needed.Mefloquine (MEF), an antimalarial agent, was previously shown to be effective against E. multilocularis in vitro and in experimentally infected mice. However, MEF is not parasiticidal and needs improvement for successful treatment of patients, and it can induce strong neuropsychiatric side-effects. In this study, the structure-activity relationship and mode of action of MEF was investigated by comparative analysis of 14 MEF derivatives. None of them showed higher activity against E. multilocularis metacestodes compared to MEF, but four compounds caused limited damage. In order to identify molecular targets of MEF and effective derivatives, differential affinity chromatography combined with mass spectrometry was performed with two effective compounds (MEF, MEF-3) and two ineffective compounds (MEF-13, MEF-22). 1′681 proteins were identified that bound specifically to MEF or derivatives. 216 proteins were identified as binding only to MEF and MEF-3. GO term enrichment analysis of these proteins and functional grouping of the 25 most abundant MEF and MEF-3 specific binding proteins revealed the key processes energy metabolism and cellular transport and structure, as well as stress responses and nucleic acid binding to be involved. The previously described ferritin was confirmed as an exclusively MEF-binding protein that could be relevant for its efficacy against E. multilocularis. The here identified potential targets of MEF will be further investigated in the future for a clear understanding of the pleiotropic effects of MEF, and improved therapeutic options against AE.